Modern NMR methodology - Matthews, Stephen; Heise, Henrike (Topics in Current Chemistry, 2013)
S. Glöggler B. Blümich S. Appelt NMR Spectroscopy for Chemical Analysis at Low Magnetic Fields U.L. Günther Dynamic Nuclear Hyperpolarization in Liquids E. Kupce NMR with Multiple Receivers Y. Xu S. Matthews TROSY NMR Spectroscopy of Large Soluble Proteins H. Müller M. Etzkorn H. Heise Solid-State NMR Spectroscopy of Proteins G. Pintacuda G. Kervern Paramagnetic Solid-State Magic-Angle Spinning NMR Spectroscopy